Gastric metastasis arising from invasive ductal and mucinous carcinoma of the breast: a case report and literature review - Lyu, Zhidong; Fei, Jie; Zhang, Longxiao; Liu, Yinbo (Frontiers in Oncology, 2025)
Gastric metastasis of breast cancer is rare, and clinical data on its treatment and prognosis are limited at present. Herein, we report a case of gastric metastasis arising from invasive ductal and mucinous carcinoma of the breast and review the literature. A 51-year-old woman was diagnosed with infiltrating and mucinous carcinoma of the right breast accompanied by ipsilateral axillary lymph node and subclavian lymph node metastases. The molecular subtype was luminal A, and the clinical stage was T4bN3M0. The patient first received 5 cycles of neoadjuvant chemotherapy, and the treatment efficacy was stable. After 3 months of treatment with abemaciclib combined with exemestane, the tumors did not significantly reduce in size. The patient underwent surgery on February 23, 2023. The postoperative pathological examination revealed Miller Payne system grade 3 (G3). Cancer metastasis (14/20) was observed in the axillary lymph nodes, and the immunohistochemical results were as follows: ER (++, 90%), PR (+, 2%), HER-2 (3+), and Ki-67 (20%). The adjuvant therapy used was exemestane combined with trastuzumab and pertuzumab. Gastric metastasis was observed 10 months after surgery. The pathological examination revealed focal atypical cell nests with disordered arrangements, indicating malignant lesions (cancer). The immunohistochemical results were as follows: GATA3 (+), ER (++, 90%), PR (-), and HER-2 (1+). In the late stage, first-line treatment with dalpiciclib and fulvestrant was administered, and liver metastasis occurred 10 months thereafter. T-DXd treatment was subsequently administered, and the patient is currently undergoing clinical follow-up. This case highlights the possibility of gastric metastasis when gastrointestinal symptoms occur in patients with a history of breast cancer.